The Effect of Agility Ladder Training on the Sickle Kick Speed of Pencak Silat Athletes of the Loyal Heart Brotherhood Terate Ngawi Branch - Arlianda Carelliva; Andy Widhiya Bayu Utomo; Arief Nur Wahyudi (Edumaspul: Jurnal Pendidikan, 2023)
Sickle kick is a kick technique that is not easy for a martial arts athlete to do, this kicking technique is more difficult compared to direct kicks or straight kicks. The sickle kick requires flexibility and speed, as well as proper practice. The purpose of this study was to determine the effect of agility ladder training method on the sickle kick speed of pencak silat athletes PerFraternity Setia Hati Terate (PSHT) Ngawi Regency. This type of research is a pseudo-experimental research that uses a non-equivalent posttest only control group design. The sample used in this study was 10 athletes divided into experimental and control classes. This data collection technique uses tests and measurements of sickle kick speed, the data that has been collected is processed and analyzed with descriptive statistics and uses t-tests to determine the results of research hypotheses. The results of this study have found that there is an effect of agility ladder training on sickle kick speed. This is indicated by a significant value (2-tailed) 0.004 < 0.005 then H1 is accepted and H0 is rejected. Scores from the sickle kick speed test results were average for the experimental group of 25 and for the control group of 20. So this means that the average experimental group > control group, so it can be concluded that the agility ladder training method can have an influence on the speed of the pencak silat sickle kick of the Brotherhood of Loyal Heart Terate Ngawi Regency